Effect of atmospheric organic complexation on iron-bearing dust solubility - R. Paris; K. V. Desboeufs (Atmospheric Chemistry and Physics, 2013)
Recent studies reported that the effect of organic complexation may be a potentially important process to be considered by models estimating atmospheric iron flux to the ocean. In this study, we investigated this process effect by a series of dissolution experiments on iron-bearing dust in the presence or the absence of various organic compounds (acetate, formate, oxalate, malonate, succinate, glutarate, glycolate, lactate, tartrate and humic acid as an analogue of humic like substances, HULIS) typically found in atmospheric waters. Only 4 of tested organic ligands (oxalate, malonate, tartrate and humic acid) caused an enhancement of iron solubility which was associated with an increase of dissolved Fe(II) concentrations. For all of these organic ligands, a positive linear dependence of iron solubility to organic concentrations was observed and showed that the extent of organic complexation on iron solubility decreased in the following order: oxalate >malonate = tartrate > humic acid. This was attributed to the ability of electron donors of organic ligands and implies a reductive ligand-promoted dissolution. This study confirms that among the known atmospheric organic binding ligands of Fe, oxalate is the most effective ligand promoting dust iron solubility and showed, for the first time, the potential effect of HULIS on iron dissolution under atmospheric conditions.